Study the effectiveness of marijuana and rosemary alchoholic extracts in control of red rusty flour beetle Tribolium castaneum (Herbst) (Col-eoptera: Tenebrionidae) - Abbas, Manar Ahmed; Alsudani, Ali Abdulridha; Alhusani, Ashwaq Hussam (Journal of Kerbala for Agricultural Sciences, 2022)
Laboratory experiments were conducted to determine the effectiveness of plant extracts of vitex and rosemary in red rust flour beetle Tribolium castaneum (Herbst) control. Results showed a significant effect of extracts oncentrations in the percentage of larval stage mortality . concentration of 5%, caused the highest mortality rates in the larval stage reached to 71.11, 76.66, 83.33 % insects / plate after 24, 48 and 72 hours, respectively. The mortality rates were equal for both concentrations 2.5 and 5%, which amounted to 90 % after 72 hours. Vitex plant extarct was significantly superior to the rosemary plant Rosmarinus officinalis in the mortality rates for all concentrations and periods post application in this study.